Pengaruh Dana Zakat, Pembiayaan Syariah, Anggaran Penerimaan dan Belanja Negara (APBN) Terhadap Tingkat Kemiskinan Dengan Indeks Pembangunan Manusia Sebagai Variabel Intervening - Febriandi Akbar Sitompul; Juliana Nasution; Imsar Imsar (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2023)
Taking into account the fluctuations in the human development index, the following conclusions can be drawn from research studying the impact of zakat money, Islamic funding, and the state budget on the poverty rate between 2010 and 2021: Zakat Funds, Islamic Finance, and Islamic Banking all contribute to reducing poverty in Indonesia between in 2010 and 2021, but the APBN has the most direct influence. In Indonesia, the State Budget, Islamic Finance, and Zakat Funds all affect the Poverty Rate and Development Index from 2010 to 2021. The Poverty Rate in Indonesia from 2010 to 2021 is Influenced by the Community's Ability to Mediate Zakat Funds, Islamic Finance, and Zakat Funds. State budget. Reducing the Role of Zakat Money, Islamic Finance, and the Indonesian Government's Budget in Creating Economic Inequality.